Higher serum ascorbic acid levels are associated with lower depression prevalence in US adults: a case-control study - Chen, Mengyuan; Luo, Haolong; Han, Yan; Li, Yuanhong; Zhou, Li; Ren, Xiangmei (Frontiers in Nutrition, 2024)
Background: Recent studies have shown that a higher intake of ascorbic acid was associated with a lower prevalence of depression. Nevertheless, the recall bias was common in dietary surveys in these studies, and it was ignored that there were differences in the absorption and utilization of ascorbic acid in the body. Hence, we aim to investigate the association between serum ascorbic acid levels and the prevalence of depression in US adults.Methods: A total of 3404 participants from the 2017-2018 National Health and Nutrition Examination Survey (NHANES) that underwent measurement of the Patient Health Questionnaire-9 (PHQ-9) scores and serum levels of ascorbic acid. Propensity Score Matching (PSM) successfully established a casecontrol study, comprising 299 participants diagnosed with depression and 1,107 as controls. We used binary logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs) to explore associated risk factors for depression. Restricted cubic splines (RCS) were used to show the nonlinear relationship between serum ascorbic acid levels and the prevalence of depression.The prevalence of depression was approximately 8.8%, with a median serum ascorbic acid level of 49.9 (36.0, 67.0) μmol/L. Results revealed that the serum ascorbic acid levels of depressed patients were significantly lower than those of non-depressed individuals (42.97 VS 52.97 μmol/L).The baseline data indicated that as serum ascorbic acid levels increased from Quartile 1 (Q1) to Quartile 4 (Q4), the depression prevalence decreased from 12.0% to 5.4% (P<0.05). The results of the chi-square test after PSM showed that serum ascorbic acid was still statistically significant (P<0.001) with the prevalence of depression. Forest plot showed that compared with the Q1 of serum ascorbic acid level, the OR and 95%CI of depression prevalence in Q4 was 0.42 (0.30 0.61), and the adjusted OR and 95%CI of depressive prevalence was 0.49 (0.33 0.73). RCS models showed an L-shaped nonlinear relationship (P for nonlinearity <0.05) between serum ascorbic acid and depression.Our results suggested that higher serum ascorbic acid levels are associated with a reduced prevalence of depression.